The optimization of passenger trains - Loboiko, L. M.; Barash, Yu. S.; Karas, O. O. (Science and Transport Progress, 2008)
In the paper the procedure of organization of traffic of day-and-night trains, various kinds of looping of passenger train sets, their drawbacks and advantages are presented.